Variation of Earthquake Ground Motions with Focus on Site Amplification Factors: A Case Study - Fukushima, Y.; Nagao, T. (Engineering, Technology & Applied Science Research, 2019)
In this paper, an evaluation of the variation of earthquake ground motions with a focus on site amplification factors based on spectral analysis is presented. By using strong motion record obtained at six sites in Japan, probability distributions of site amplification factors were shown. The relations between standard deviations of site amplification factors and distances between the sites were studied. The variations of representative values of earthquake ground motions based on the variations of site amplification factors were discussed by using probabilistic seismic hazard analysis with focus on Fourier amplitude and group delay time. The distributions of peak ground accelerations and peak ground velocities were shown. It is suggested that design earthquake ground motions considering the average site amplification factors may lead the engineering design on the dangerous side.